Effects of the evidence-based history teaching on Turkish primary students' perception of history and related concepts - KABAPINAR, YÜCEL (ELSEVIER SCIENCE BV, 2010)
The purpose of this study is to determine the effects of evidence-based history teaching on students' perception of the history and related concepts. The study was conducted as an action research. A teaching intervention was designed. The main theoretical perspective informing the teaching intervention was evidence-based history teaching. The teaching intervention was put into practice in a 8th grade class consisting of 25 primary students (aged 14-15). It lasted 15 teaching hours. The effectiveness of the teaching intervention was determined by using both a questionnaire consisting of open-ended questions and worksheets used during the teaching intervention. Students completed the same questionnaire, designed by the researchers, prior to and after the teaching intervention. Additionally, students' works as in the form of worksheets were collected and analysed so as to find out effectiveness of the specific teaching activities. The descriptive and content analyses methods were employed in analysis of data collected. The findings of the study indicated that students' perceptions on history and related concepts changed as result of evidence-based history teaching used in their courses. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Historical evidence; history teaching; action research; Turkish students